Evaluating the Technical Efficiency of Dairy Farms Under Technological Heterogeneity: Evidence from Lithuania - Rūta Savickienė; Virginia Namiotko; Aistė Galnaitytė (Agriculture)
The European Union’s (EU) Common Agricultural Policy aims to promote sustainable farming practices that ensure the responsible use of natural resources, safeguard biodiversity, and uphold higher animal welfare standards. One pathway to achieving these objectives is through the encouragement of extensive farming. However, the dairy sector in EU countries as well as in Lithuania has shown a clear trend toward intensification. The aim of this study was to assess the technical efficiency (TE) of dairy farms employing extensive and intensive technologies. TE was evaluated using Data Envelopment Analysis (DEA) combined with meta-frontier analysis, which accounts for technological heterogeneity. Prior to the efficiency estimation, farms were grouped into two distinct categories—intensive and extensive—using the k-means clustering algorithm. The empirical results show that extensive dairy farms in Lithuania are smaller in land area and livestock units, rely more on internal resources, and exhibit lower productivity compared to intensive farms. Intensive farms achieved higher technical efficiency, narrower technological gaps, and more optimal scale efficiency, indicating superior resource management. The weaker performance of extensive farms is attributed to both less advanced technologies and production inefficiencies.